Journal of the Australian Ceramic Society - Vance, Eric.; Ben-Nissan, Besim; Sorrell, Charles; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Covers the fields of ceramic technology, basic science and related materials, including new advances in ceramic materials.
Keywords: Inorganic chemistry; Engineering -- Materials; Ceramics; Glass; Composites (Materials).; Composite materials; Ceramics, Glass, Composites, Natural Materials; Materials Engineering; Inorganic Chemistry